A Low-Cost Laser Barrier Based Vectorial Velocity Measurement System - Lindner, Stefan; Weigel, Robert; Kölpin, Alexander (IEEE Sensors, 2016)
This paper describes a low-cost measurement system based on two crossed laser barriers to measure the angle, the position as well as the velocity of an object with known shape, which is passing the measurement system. Due to the simple system setup this leads to a low-cost vectorial speed measurement system, which is capable of high speed measurements. Furthermore, as a demonstrator, a table soccer ball speed measurement system will be presented, which shows the feasibility of the proposed system.
elib2cris::1512001600,lindner2016
Keywords: angle of arrival; velocity measurement; laser barrier; crossed laser; table soccer